An Image-Based Prior Knowledge-Free Approach for a Multi-Material Decomposition in Photon-Counting Computed Tomography - Neumann, Jonas; Nowak, Tristan; Schmidt, Bernhard; von Zanthier, Joachim (Diagnostics, 2024)
Photon-counting CT systems generally allow for acquiring multiple spectral datasets and thus for decomposing CT images into multiple materials. We introduce a prior knowledge-free deterministic material decomposition approach for quantifying three material concentrations on a commercial photon-counting CT system based on a single CT scan. We acquired two phantom measurement series: one to calibrate and one to test the algorithm. For evaluation, we used an anthropomorphic abdominal phantom with inserts of either aqueous iodine solution, aqueous tungsten solution, or water. Material CT numbers were predicted based on a polynomial in the following parameters: Water-equivalent object diameter, object center-to-isocenter distance, voxel-to-isocenter distance, voxel-to-object center distance, and X-ray tube current. The material decomposition was performed as a generalized least-squares estimation. The algorithm provided material maps of iodine, tungsten, and water with average estimation errors of 4% in the contrast agent maps and 1% in the water map with respect to the material concentrations in the inserts. The contrast-to-noise ratio in the iodine and tungsten map was 36% and 16% compared to the noise-minimal threshold image. We were able to decompose four spectral images into iodine, tungsten, and water.
CRIS-Team Scopus Importer:2024-07-12
Keywords: computed tomography; k-edge imaging; multi-material decomposition; photon-counting ct; photon-counting detector; spectral ct

Photon-Counting Computed Tomography-Based Hepatic iron Quantification Using a Tungsten-Based Contrast Agent - Neumann, Jonas; Haubold, Johannes; Jergas, Felix; Jost, Gregor; Pietsch, Hubertus; Schmidt, Bernhard; Nowak, Tristan; von Zanthier, Joachim (Investigative Radiology, 2025)
Objectives This study explores the potential of quantifying hepatic iron in computed tomography (CT) scans in the presence of iodine (I)- or tungsten (W)-based contrast media (CM). Materials and Methods Experimental work was performed on a commercial photon-counting CT system able to simultaneously acquire up to 4 spectral data sets in a single scan. We examined 2 anthropomorphic abdominal phantoms with material samples of liquid liver tissue surrogate, fat, iron, and I- or W-based CM to mimic different liver compositions in an enhanced CT scan. Iron was quantified by material decomposition of reconstructed spectral CT images. Results Two-material decomposition based on 2 spectral data sets provided material images of iron and liver with an accuracy of 1.4 mg/mL in the iron image of CM-free samples. The presence of W affected the iron quantification: For 2 and 4 mgW/mL in the material samples, the iron concentration was overestimated (P < 0.05) with accuracies of 2.7 and 4.7 mg/mL, respectively. Three-material decomposition based on 4 spectral data sets provided material images of iron, liver, and W, with an accuracy of 1.4 mg/mL in the images without W and 1.5 (nonsignificant difference, P > 0.07) and 1.6 mg/mL (overestimation, P > 0.03) in the iron image at 2 and 4 mgW/mL, respectively. The presence of I affected the iron quantification more than W in both 2- and 3-material decomposition: For 2 and 4 mgI/mL in the material samples, the measured iron concentration was even higher (P < 0.05), with accuracies >18 and >37 mg/mL, respectively. Conclusions The accuracy of iron quantification from a 3-material decomposition suggested clinically feasible detection and quantification of critical hepatic iron levels in enhanced CT scans with suitable CM. In a 2-material decomposition, severe pathology is required to detect an iron liver. W-based CM was superior to I-based CM.
CRIS-Team Scopus Importer:2025-05-02
Keywords: computed tomography; contrast media; iron quantification; liver; multimaterial decomposition; photon counting CT; spectral CT; tungsten